Дослідження порогових характеристик зору при використанні освітлювальних установок з різними типами джерел світла - Таряник, М.М.; Сіробаба, О.О.; Овчинников, С.С. (Технічна електродинаміка, 2011)
Threshold values of illumination produced by different sources under illumination fluctuation and visual processes under superthreshold and before-threshold fluctuations have been defined.